Investigation of in-vitro antioxidant potential in crotalaria verrucosa along with identification and quantification of its polyphenolic compounds - Ahmed, Zainab Syed (BRAC University, 2017)
This project report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Pharmacy, 2016